Associations of delirium with urinary tract infections and asymptomatic bacteriuria in adults aged 65 and older: A systematic review and meta‐analysis. Issue 11 (27th August 2021) - Krinitski, Damir; Kasina, Rafal; Klöppel, Stefan; Lenouvel, Eric
Abstract: Objective: To determine the associations of delirium with urinary tract infection (UTI) and asymptomatic bacteriuria (AB) in individuals aged 65 and older. Methods: The protocol for this systematic review and meta‐analysis was published on PROSPERO (CRD42020164341). Electronic databases were searched for relevant studies, professional associations and experts in the field were additionally contacted. Studies with control groups reporting associations between delirium and UTI as well as delirium and AB in older adults were included. The random effects model meta‐analysis was conducted using odds ratios (ORs) with 95% confidence intervals (CIs) as effect size measures. The Newcastle‐Ottawa scale was used to rate the studies' quality. Heterogeneity was assessed using the Q and I 2 tests. The effects of potential moderators were investigated by both subgroup and meta‐regression analyses. The risk of publication bias was evaluated using the funnel plot and Egger's test. Results: Twenty nine relevant studies (16, 618 participants) examining the association between delirium and UTI in older adults were identified. The association between delirium and UTI was found to be significant (OR 2.67; 95% CI 2.12–3.36; p  < 0.001) and persisted regardless of potential confounders. The association between delirium and AB in older adults in the only eligible study found (192 participants) was insignificant (OR 1.62; 95% CI 0.57–4.65; p  = 0.37). All included studies were of moderate quality. Conclusion: The results of this study support the association between delirium and UTI in older adults. Insufficient evidence was found to conclude on an association between delirium and AB in this age group. These findings are limited due to the moderate quality of the included studies and a lack of available research on the association between delirium and AB. Future studies should use the highest quality approaches for defining both delirium and UTI and consider AB in their investigations.